Enhancement of the sensitivity of a microbial fuel cell sensor by transient-state operation. Issue 3 (10th February 2017) - Jiang, Yong; Liang, Peng; Liu, Panpan; Miao, Bo; Bian, Yanhong; Zhang, Helan; Huang, Xia
Abstract : The transient-state operation mode was applied in an MFC sensor and was further proved applicable for three kinds of detections with higher sensitivity. Abstract : One of the main challenges of using a microbial fuel cell (MFC) sensor is its relatively poor sensitivity, which can cause a potential fault warning when used for water monitoring. To address this limitation, this study provides a new transient-state operation mode for an MFC sensor, which is proved applicable for three kinds of detections with higher sensitivity. Under the transient-state mode, the sensitivity increases by 50% to 247% when testing organic matter, acidic toxicants and heavy metals, compared to that of an MFC sensor in conventional constant external resistance connected mode. The mechanism for the improvement is analyzed both experimentally and with an equivalent circuit model. To obtain a higher sensitivity, the output signal of U on (connected to the external resistance) is more adapted for organic matter monitoring with a wider range, while the output signal of U off (disconnected to the external resistance) is better for toxicity monitoring.